2013
DOI: 10.3109/17482941.2013.776690
|View full text |Cite
|
Sign up to set email alerts
|

Time of day variation in door-to-balloon time for STEMI patients in Los Angeles County: Does time of day make a difference?

Abstract: In STEMI patients receiving primary PCI in Los Angeles County, off-hour PCI was common. Short-term clinical outcomes were similar despite longer door-to-balloon time in patients receiving off-hour PCI. The longer door-to-balloon time in the off-hour PCI patients were partly explained by longer door-to-CL activation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Investigation the correlation of time from initial assessment to emergency department until the onset of primary angioplasty with the final outcome in patients with acute myocardial infarction was evaluated in all studies included in the review. In majority of cases, primary angioplasty was achieved initiation time of less than 90 minutes from the initial assessment, resulting in better outcomes of patients (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in case of performing culprit-vessel primary percutaneus coronary intervention before the unilateral or complete diagnostic angiography is associated with a statistically significant reduction in vascular access-to-balloon time, although the difference of 4-6 minutes is unlikely to be clinically relevant (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigation the correlation of time from initial assessment to emergency department until the onset of primary angioplasty with the final outcome in patients with acute myocardial infarction was evaluated in all studies included in the review. In majority of cases, primary angioplasty was achieved initiation time of less than 90 minutes from the initial assessment, resulting in better outcomes of patients (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in case of performing culprit-vessel primary percutaneus coronary intervention before the unilateral or complete diagnostic angiography is associated with a statistically significant reduction in vascular access-to-balloon time, although the difference of 4-6 minutes is unlikely to be clinically relevant (22).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one in two AMI cases are fatal before admittance in hospital and occur more frequently within one hour of the onset of symptoms (26), whereas delayed onset of primary angioplasty by over two hours increases mortality (29). This review showed that in most cases primary angioplasty was achieved start within 90 minutes from the initial assessment, resulting in better outcomes of patients and agreement with the target time of guidelines (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, conflicting research has shown that short-term clinical outcomes for PCI patients were similar, despite longer D2B times in patients receiving after-hour PCI. 18 Circadian variation has also been shown to impact both frequency of MI onset and infarct size. 19 Similarly, myocardial infarct size and left ventricular function after STEMI have been shown to have a circadian dependence on the time of day onset of ischemia.…”
Section: Introductionmentioning
confidence: 99%